2017
DOI: 10.1002/acr.23192
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profiles of Young Adults With Juvenile‐Onset Fibromyalgia With and Without a History of Trauma

Abstract: Objective The primary objectives of this study were to examine the differential presentation(s) in young adults with Juvenile-onset Fibromyalgia (JFM) with and without a history of trauma as compared to healthy controls across psychological and health-related outcomes. Methods 110 participants (86 with JFM and 24 healthy controls; Mage=23.4 years) completed a structured clinical interview to assess for trauma and psychological comorbidities and self-report questionnaires on pain, physical functioning, and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 41 publications
2
19
0
Order By: Relevance
“…Depressive symptoms, pain intensity, and functional disability were not statistically or clinically significantly different between PTSD groups, although the functional disability was trending towards significance. These findings are generally consistent with previous research on the effects of psychological trauma and/or PTSD on pediatric or young adult chronic pain populations in that trauma/PTSD history has been most commonly found to affect psychosocial functioning vs. physical functioning [ 1 ]. However, previous research on chronic pain and posttraumatic stress symptoms (PTSS) found a strong association between PTSS and facets of the pain experience, including intensity, interference, and unpleasantness [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Depressive symptoms, pain intensity, and functional disability were not statistically or clinically significantly different between PTSD groups, although the functional disability was trending towards significance. These findings are generally consistent with previous research on the effects of psychological trauma and/or PTSD on pediatric or young adult chronic pain populations in that trauma/PTSD history has been most commonly found to affect psychosocial functioning vs. physical functioning [ 1 ]. However, previous research on chronic pain and posttraumatic stress symptoms (PTSS) found a strong association between PTSS and facets of the pain experience, including intensity, interference, and unpleasantness [ 16 ].…”
Section: Discussionsupporting
confidence: 90%
“…Youth with chronic pain report higher rates of psychological trauma (abuse, neglect, violent or conflictual home environment, etc.) when compared to the average population or healthy controls [ 1 , 2 ]. In particular, functional abdominal pain disorders (FAPDs), which are common, persistent, and/or recurrent abdominal pain conditions without a clear organic etiology, are worthy of further investigation in relation to trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, post‐traumatic stress symptoms (PTSS) and post‐traumatic stress disorder (PTSD) are common in youth following burn injury (18%–25%; Corry et al., ; De Young, Kenardy, Cobham, & Kimble, ; Landolt, Buehlmann, Maag, & Schiestl, ) and can be observed in children as young as 12 months old (Stoddard et al., ). Consistent with this line of research, evidence suggests that youth with chronic pain report high exposure to psychological trauma or adverse childhood experiences (Nelson, Simons, & Logan, ; Nelson et al., ; Walker et al., ) and many report experiencing PTSS (Holley, Wilson, Noel, & Palermo, ; Noel et al., ). Similar to other psychological symptoms, the relationship between the experience of pain and trauma or post‐traumatic stress may be bidirectional.…”
Section: Resultsmentioning
confidence: 84%
“… 13 However, few studies have examined the prevalence of ACEs and their relationship to chronic pain among children in the United States. Indeed, research to date has focused on a few specific clinical pain samples including fibromyalgia, 15 abdominal pain, 11 complex regional pain syndrome, 28 and migraine headache 8 and those presenting for multidisciplinary chronic pain management. 18 Taken together, the evidence available suggests that youth with chronic pain conditions report ACEs more frequently than youth without chronic pain.…”
Section: Introductionmentioning
confidence: 99%